2014
DOI: 10.1111/clr.12439
|View full text |Cite
|
Sign up to set email alerts
|

Fixed restorations supported by Morse‐taper connection implants: a retrospective clinical study with 10–20 years of follow‐up

Abstract: Satisfactory "complication-free" survival rates can be achieved after 20 years for fixed restorations supported by Morse-taper connection implants, with minimal marginal bone loss and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 47 publications
2
71
0
3
Order By: Relevance
“…Although a large number of studies report favorable survival rates with the use of dental implants in various situations, complications of organic and prosthetic nature could affect implant-supported restorations, especially in the long term (13).…”
Section: Discussionmentioning
confidence: 99%
“…Although a large number of studies report favorable survival rates with the use of dental implants in various situations, complications of organic and prosthetic nature could affect implant-supported restorations, especially in the long term (13).…”
Section: Discussionmentioning
confidence: 99%
“…Locking-taper implants have demonstrated mechanical advantages over screw-type, buttjoint connections: they can resist eccentric loads and bending moments, ensuring a remarkable stability, as demonstrated in several studies [22,23]. Different clinical studies have found a low incidence of prosthetic complications when locking-taper implants were used [24][25][26][27][28][29][30][31]. Only a few studies, however, have reported on the incidence of biological and prosthetic complications encountered with locking-taper implants in the long-term [28][29][30][31], and little is known about the long-term clinical outcomes of SCs supported by locking-taper implants [29].…”
Section: Introductionmentioning
confidence: 99%
“…Different clinical studies have found a low incidence of prosthetic complications when locking-taper implants were used [24][25][26][27][28][29][30][31]. Only a few studies, however, have reported on the incidence of biological and prosthetic complications encountered with locking-taper implants in the long-term [28][29][30][31], and little is known about the long-term clinical outcomes of SCs supported by locking-taper implants [29]. An interesting way to describe the susceptibility to complications, whether biological or prosthetic, is to report the "complication-free" survival rate of restorations [28,31,32] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations